Combined Conjoint Analysis and Cluster Analysis in Segmentation of College Student Housing Preferences: (Study of Statistics Students at Universitas Brawijaya Class of 2020-2023) (Universitas Brawijaya, 2024)
Housing is a primary need for students who study outside their hometown. In choosing a place to live, students are faced with various choices. The aim of the research is to determine the main factors that influence students preferences in choosing a place to live using conjoint analysis and segmentation produced based on the results of preferences using cluster analysis. The research uses primary data taken using an online questionnaire from undergraduate students at the Department of Statistics, FMIPA UB Class of 2020 – 2023 who have chosen a place to live/rental housing. The number of samples was determined using a purposive sampling technique of 100 respondents. There are seven attributes used, namely Type of Residential, Distance to University, Rental Price, Residential Regulations, Residential Location, Residential Facilities, and Payment Period. The research results show that the most important attribute in determining preferences for choosing housing/rental housing by students is the Rental Price attribute with a level of less than IDR 1,000,000 per month. The combination of respondent level preferences is the type of boarding house, distance to campus close (around 1 – 3 km), rental price less than IDR 1,000,000 per month, residential regulations have no curfew, residential location is located in a rental residential area, complete residential facilities (Wi-Fi, private bathroom, parking, air conditioning, study table), and monthly payment period. After conducting cluster analysis, six segments were formed. The most important attributes in determining preferences for each segment are the residential facility attributes, rental price, distance to campus, type of housing, and residential regulations.